Executive summary of the American Radium Society appropriate use criteria for management of uterine clear cell and serous carcinomas. Issue 12 (24th November 2022) - Sherertz, Tracy; Jhingran, Anuja; Biagioli, Matthew; Gaffney, David; Elshaikh, Mohamed; Coleman, Robert L; Harkenrider, Matthew; Kidd, Elizabeth A; Jolly, Shruti; Yashar, Catheryn; Portelance, Lorraine; Wahl, Andrew; et al.
Abstract : Background: Uterine clear cell and serous carcinomas have a high propensity for locoregional and distant spread, tend to be more advanced at presentation, and carry a higher risk of recurrence and death than endometrioid cancers. Limited prospective data exist to guide evidence-based management of these rare malignancies. Objective: The American Radium Society sought to summarize evidence-based guidelines developed by a multidisciplinary expert panel that help to guide the management of uterine clear cell and serous carcinomas. Methods: The American Radium Society Appropriate Use Criteria presented in this manuscript were developed by a multidisciplinary expert panel using an extensive analysis of current published literature from peer-reviewed journals. A well-established methodology (modified Delphi) was used to rate the appropriate use of diagnostic and therapeutic procedures for the management of uterine clear cell and serous carcinomas. Results: The primary treatment for non-metastatic uterine clear cell and serous carcinomas is complete surgical staging, with total hysterectomy, salpingo-oophorectomy, omentectomy, and lymph node staging. Even in early-stage disease, patients with uterine clear cell and serous carcinomas have a worse prognosis than those with type I endometrial cancers, warranting consideration for adjuvant therapy regardless of the stage. Given the aggressive nature of these malignancies, and until further research determines the most appropriate adjuvant therapy, it may be reasonable to counsel patients about combined-modality treatment with systemic chemotherapy and radiotherapy. Conclusion: Patients diagnosed with uterine clear cell and serous carcinomas should undergo complete surgical staging. Multimodal adjuvant therapies should be considered in the treatment of both early-stage and advanced-stage disease. Further prospective studies or multi-institutional retrospective studies are warranted to determine optimal sequencing of therapy and appropriate management of patients based on their unique risk factors. Long-term surveillance is indicated due to the high risk of locoregional and distant recurrence.